Flow of nanofluid past a stretching cylinder subject to Thompson and Troian slip in the presence of gyrotactic microorganisms - Puneeth, V.; Sini, Katharin; Clair, Tom; Anwar, M. Shoaib (Multiscale and Multidisciplinary Modeling, Experiments and Design, 2025)
Incorporating the Thompson and Troian slip condition, this work studies the bioconvective flow of a nanofluid past a vertically stretching cylinder. The Thompson and Troian slip deals with the molecular scale interactions at the solid–fluid interface, which plays a pivotal role in the fluid flow analysis. This study helps in understanding the behaviours of fluid flow in the presence of non-linear slip past a vertically stretching cylinder. The corresponding partial differential equations (PDEs) for momentum, energy, concentration of nanoparticles, and concentration of microbes are developed using Buongiorno’s model. A suitable similarity transformation is then applied to these PDEs, converting them into a set of ordinary differential equations (ODEs). The Runge–Kutta–Fehlberg (RKF-45) method is utilized to calculate the numerical solution of the resulting ODE problem. The results demonstrate that the interaction of slip conditions, viscous dissipation, heat source, and bioconvection causes complex flow patterns and heat transfer characteristics. These observations are extremely relevant for applications including better oil recovery procedures, biomedical engineering, and microfluidic devices where exact control over nanofluid behaviour is necessary. Some of the major observations of the study include the enhancement of the temperature in the nanofluid for higher Eckert numbers, control of fluid flow through an external magnetic field, and Peclet number significantly decreased the motile density in the nanofluid.